Supporting Policies for the Renewal of Public Vehicle Fleets to Achieve Efficient Carbon Mitigation - Princz-Jakovics, Tibor; Horváth , György Ádám (European Journal of Sustainable Development, 2023)
The aim of the research is to establish an assessment framework for evaluating transport-related carbon emission reduction options. The reduction of fleet-related emissions must build momentum, as the transport sector remains a substantial contributor to global carbon emissions. Through the use of this framework, better supporting policy for the transition of public service vehicle fleets to electromobility would be prepared. The greatest impact for investment can be achieved by facilitating the transition of vehicles with the largest distances driven. Hence, careful consideration of the operational conditions and the level of efficiency of different modes of public transport would be subject of analysis. The energy consumption of public vehicles can be calculated on the basis of the specific fuel consumption patterns and operational data of fleets. This method can be used to estimate the decarbonisation potential of different vehicle types, which may nevertheless differ significantly. The assessment framework will make abatement costs comparable and provide a basis for the targeted application of supporting policies. As preference should be given to vehicles with the lowest marginal abatement costs to effectively reduce the sector's carbon emissions, these must be identified. The theoretical contribution of this research is an evaluation framework that provides relevant data for decision makers to assess the long-term financial and social impacts of different public fleet renewal supporting strategies. Keywords: assessment framework, emission calculations, electromobility, supporting policies, marginal abatement costs.